Studi Perbandingan Prestasi Belajar antara Siswa Yang Diajar dengan Menggunakan Metode Pemecahan Masalah dan Metode Conseptual Understanding Procedures (CUPs) pada Siswa Kelas VII SMP Negeri 14 Buton Tengah - Neli Asriani Ukus; Dian Lestari; Suwarni La Usa (Jurnal Akademik Pendidikan Matematika, 2023)
The aim of this research is to find out the differences in student achievement who are taught by using the Problem Solving method and the Conceptual Understanding Procedures (CUPs) method for the seventh grade students of SMPN 14 Buton Tengah. This research is a quantitative quasi-experimental method. The population of this study were all seventh grade students of SMP Negeri 14 Buton Tengah for the academic year 2021/2022 which consisted of two classes, namely 46 students. The sampling technique used was saturated sampling technique, where all members of the population were used as samples. The data collection in this research is the giving of students’ mathematics achievement tests to both classes after all learning subjects are completed, with problem solving methods and Conceptual Understanding Procedures (CUPs) methods. The data analysis technique in this study used descriptive statistics and inferential statistics. The results of the descriptive analysis of the mathematics learning achievement of the experimental class I students obtained an average value of 83.91 and the average mathematics learning achievement of the experimental class II students was 75.43. Data processing in inferential statistics with t-test obtained the value of tcount = 2.120 with df = 44 sig. (2-tailed) at 0.040 < (0.05) so that it can be concluded that there is a significant difference between the mathematics learning achievement of students who are taught using problem solving methods and the method of Conceptual Understanding Procedures (CUPs) in class VII students of SMP Negeri 14 Buton Tengah.